Aesthetics of the Environment and Environmental Aesthetics - Iannilli, Gioia Laura (Aesthetica Preprint, 2020)
The thesis underlying this paper is that “the aesthetic” intrinsically possesses an environmental feature (and that therefore this latter should be a feature of aesthetics, too). In order to prove this claim viable I will tackle the implications of a so-called “environmental tension” in aesthetics. This tension, signaling a specific “environmental momentum” for contemporary aesthetics, will be understood in a threefold sense. First, in the sense of a relationship between academic/theoretical/thematic and practical/operative environmental aesthetics emphasizing the pluralistic character of the aesthetic. Second, in the sense of a relationship between backgrounds and foregrounds in aesthetic experience emphasizing the potential character of the aesthetic. Third, in the sense of a relationship between quantities and qualities in aesthetic experience emphasizing the irreducible first-hand, situated, or embedded character of the aesthetic. Ultimately, I will give an overview of seven different theoretical endeavors carried out in the framework of contemporary Italian aesthetics addressing the topic of “aesthetic environments” and whose common denominator – as I shall try to show – is precisely the environmental feature of the aesthetic and aesthetics.